Financial Reforms and Interest Rate Spreads in the Commercial Banking System in Malawi - Chirwa, Ephraim; Mlachila, Montfort (Washington, D.C. : International Monetary Fund, 2002)
This study investigates the impact of financial sector reforms on interest rate spreads in the commercial banking system in Malawi. The financial reform program commenced in 1989 when both the Reserve Bank Act and the Banking Act were revised with the easing of entry requirements into the banking system, and indirect monetary policy instruments were subsequently introduced in 1990. The adoption of a floating exchange rate in 1994 marked the end of major policy reforms in the Malawian financial sector. Using alternative definitions of spreads, our analysis shows that spreads increased significantly following liberalization, and panel regression results suggest that the observed high spreads can be attributed to high monopoly power, high reserve requirements, high central bank discount rate and high inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet